2017
DOI: 10.1039/c7ta07012h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defects in copper antimony disulfide

Abstract: Copper antimony disulfide (CuSbS2) has several excellent bulk optoelectronic properties for photovoltaic absorber applications. Here, we report on the defect properties in CuSbS2 thin film materials and photovoltaic devices studied using several experimental methods supported by theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…Besides, the PL spectra of all three samples comprised two different peaks, located at approximately 1.25 and 1.35 eV, which present a slightly red shift compared with the published theoretical simulation and experimental result of 1.5 eV. It has been reported that there are acceptor defects of Cu Sb anti‐site and V S (sulfur vacancy) located at 0.25 and 0.15 eV, respectively, above the CuSbS 2 valance band maximum which is consistent with the difference between our result and the literature report . Therefore, we speculate these kinds of shallow defects cause red‐shifted peaks.…”
Section: Resultssupporting
confidence: 90%
“…Besides, the PL spectra of all three samples comprised two different peaks, located at approximately 1.25 and 1.35 eV, which present a slightly red shift compared with the published theoretical simulation and experimental result of 1.5 eV. It has been reported that there are acceptor defects of Cu Sb anti‐site and V S (sulfur vacancy) located at 0.25 and 0.15 eV, respectively, above the CuSbS 2 valance band maximum which is consistent with the difference between our result and the literature report . Therefore, we speculate these kinds of shallow defects cause red‐shifted peaks.…”
Section: Resultssupporting
confidence: 90%
“…The defects in CuSb(S/Se) 2 system acts as trap for electron and hole charge carriers. The capture cross‐section area for electron and holes are considered 2 × 10 −12 cm −2 in this simulation, which is in good agreement with the experimentally observed results . The impact of the bulk defect density and the interface defect density are summarized in Figure 6A,B, respectively.…”
Section: Materials Parameters and Device Structuresupporting
confidence: 84%
“…Other acceptor defects in CuSb(S/Se) 2 may appear because of antisite defects, where Cu is present at Sb site (Cu Sb ). These defect levels are approximately 0.1 to 0.2 eV deep above valence band . The donor defects introduced by the interstitial Copper (Cu i ) in the CuSb(S/Se) 2 are shallow and close to the conduction band minima.…”
Section: Materials Parameters and Device Structurementioning
confidence: 99%
See 2 more Smart Citations